OS CUSTOS DA EPIDEMIA DA OBESIDADE: Foco na Prevenção - Marco António da Costa Coelho (2022)
Obesity is not just a problem in its own right, but also a disease with several associated comorbidities, whose prevalence continues to rise. Obesity has a negative impact on health and therefore on the economy. In addition, it is largely preventable. This article discusses its costs and explores ways to reduce them, particularly by preventing overweight and obesity. The costs associated with obesity reach very high values - $275 billion per year in the United States of America (USA) and around €70 billion in Europe, which can account for more than 20% of annual health expenditure costs, including direct and indirect costs. In addition, the comorbidities of obesity, especially cardiovascular diseases and type 2 diabetes mellitus, justify a large proportion of the associated expenses. It has been estimated that halting the rise in the prevalence of obesity would be enough for huge cost savings. It has also been shown that obesity prevention strategies through community-based programs to promote physical activity and improve nutritional status are associated with an important financial return. For example, they may represent a return 5.6 times higher than the investment made. Obesity prevention strategies can take place at the various prevention levels. However, although some evidence of its cost-effectiveness is accumulating, there is still a long way to go for its global and systematic implementation with the potential to transform the approach to obesity towards the provision of value-based health care.